Production of lactic acid from tapioca sugars - Nurfaziela, Binti Onet (Universiti Malaysia Sarawak, UNIMAS, 2012)
Tapioca (Manihot esculenta) also known as ubi kayu among Malaysian is a starchy plant material that can be hydrolyzed to produced reducing sugars by bacterial enzymes. Subsequently, these reducing sugars can be fermented to produce lactic acid using Lactococcus lactis IO-1. Exactly 500g of FT was added to 1000ml of distilled water. Then, the mixture is enzymatically hydrolysed, filtered and autoclaved to produce tapioca sugar syrup. Enzymatic hydrolysis of FT and TF were carried out in 2 stages namely liquefaction and saccharification with help of enzymes Termamyl-SC and Dextrozyme under optimum conditions. The tapioca sugar with different concentration (50g/L, 100g/L and 150g/L) were used in batch fermentation using 10% of inoculum of Lactococcus lactis IO-1 in production of lactic acid. The glucose recovery from both FT and TF were compared, and glucose recovery from TF was higher (62.7% to 68.1%) than FT (39.3% to 45.4%). Then lactic acid production from TFS and FTS were compared under three glucose concentrations (50g/L, 100g/L and 150g/L). Glucose concentration at 50g/L of FT showed the highest fermentation efficiency (29.91%) and lactic acid production (10.42g/L) than 100g/L and 150g/L of FT at 2.80% and 1.67%, respectively. The high fermentation efficiency (12.90%) and lactic acid production (6.31g/L) also derived from 50g/L of TFS. Therefore, FTS with concentration of 50g/L has high possibility in maximizing the lactic acid production (29.91%) and show economical potential compared to TFS although its glucose recovery (39.3% to 45.4%) was low than TFs (62.7% to 68.1%).